Carbon nanorod supported metal alloy nanocubes using polydopamine as location reagent for water splitting. (22nd October 2021) - Ning, Guyang; Fu, Mingxuan; Liu, Jiaxian; Sun, Yuena; Lu, Haijun; Wang, Haiyang; Fan, Xinyu; Zhang, Yufan; Wang, Huan
Abstract: Transition metal catalysts were supposed to be the most likely substitute for commercial noble metal catalysts, and the development of highly active and long-term catalyst for water splitting are the future trend. Herein, Ni rectangular nitrogen doped carbon nanorods@Fe–Co nanocubes (Ni-CNRs@Fe–Co cubes) were fabricated via a facile template-free method. This simple strategy not only realizes the structure tailoring, but also achieves high-quality nitrogen-doping. Specifically, nickel dimethylglyoxime [Ni(dmg)2 ] with rectangular rodlike structure was firstly synthesized by solution method, then metal-organic frameworks Fe–Co nanocube with different contents were loaded on rectangular carbon nanorods with polydopamine as the locating and the connecting agent, and finally Ni-CNRs@xFe-Co cubes were obtained by a one-step calcination. A series of electrochemical tests were researched on materials with different metal contents in the 1 M KOH solution. The Ni-CNRs@Fe–Co cubes show excellent electrocatalytic activity in the hydrogen evolution reaction (HER) and the oxygen evolution reaction (OER). For HER and OER, the Tafel slopes were 83.3 mV dec −1 and 71 mV dec −1, the onset potential were −167 mV and 1.62 V, and reached the current densities of 10 mA cm −2, the overpotential just needed 196 mV and 433 mV, respectively. This novel synthetic strategy will provide a template-free way for cheap electrocatalysts of non-precious metal for OER and HER. Graphical abstract: Ni rectangular nitrogen doped carbon nanorods@Fe–Co nanocubes (Ni-CNRs@Fe–Co cubes) as effective electrocatalysts for hydrogen evolution and oxygen evolution. Image 1 Highlights: Fe–Co nanocubes were loaded on rectangular carbon nanorods. Polydopamine as location reagent to anchor Fe–Co MOFs on the Ni-CNRs. Alloy formation, nitrogen doping and reduction simultaneously realized. High electrocatalytic performance for both HER and OER in alkaline media.